ADC value and diffusion tensor imaging of prostate cancer: Changes in carbon-ion radiotherapy - Takayama, Yukihisa; Kishimoto, Riwa; Hanaoka, Shouhei; Nonaka, Hiroi; Kandatsu, Susumu; Tsuji, Hiroshi; Tsujii, Hirohiko; Ikehira, Hiroo; Obata, Takayuki (Journal of magnetic resonance imaging, 2008)
Purpose To assess the apparent diffusion coefficient (ADC) value and diffusion tensor image (DTI) including fractional anisotropy (FA) of the noncancerous prostate and prostate cancer before and after carbon‐ion radiotherapy (CIRT). Materials and Methods Nine patients with biopsy‐proven prostate cancer underwent 1.5T magnetic resonance (MR) examinations. One patient with benign prostatic hypertrophy and one healthy volunteer were also examined as references. The changes in ADC values and DTI of the entire prostate calculated from b‐values of 0 and 700 (s/mm2) were estimated between before and after CIRT. Results ADC values of prostate cancer significantly increased after CIRT by paired t‐test (P < 0.01) but those of noncancerous inner gland (IG) and peripheral zone (PZ) showed no significant change. By analysis of variance, significant differences in ADC values were observed among prostate cancer and noncancerous IG and PZ before CIRT (P < 0.05). After CIRT, those significant differences had disappeared. FAs showed no significant differences in any comparisons. DTI showed changes in the direction of the main axis of the tensor in prostate cancer after CIRT. Conclusion There were changes in ADC and DTI in prostate cancer after CIRT. They may be useful for monitoring prostatic structural changes under radiotherapy. J. Magn. Reson. Imaging 2008;27:1331–1335. © 2008 Wiley‐Liss, Inc.